2020
DOI: 10.9734/ijpr/2020/v4i330112
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Parasitaemia and Variations in Haematological Parameters among Pregnant Women in Buea

Abstract: Background: Malaria is a life threatening parasitic disease that is entirely preventable and curable. Pregnant women are among the most vulnerable groups to this deadly disease. Prompt diagnosis and treatment is needed to reduce morbidity and mortality. Haematological changes that occur during malaria infection have been suggested as a potential predictor that can aid in the diagnosis of malaria infection. Methods: A cross sectional study involving 276 pregnant women with signs and symptoms of malaria wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In another hospital-based cross-sectional study in a region of Ghana, red cell and platelet counts were signi cantly lower in malaria than non-malaria infected patients (14). Ndamukong-Nyanga et al noted similar ndings in another cross-sectional study in Buea, Cameroon (22). They noted thrombocytopenia and anaemia to be the most signi cant predictors of malaria in their study region and concluded that these parameters could improve malaria diagnosis when utilised in conjunction with other clinical features.…”
Section: Discussionmentioning
confidence: 68%
“…In another hospital-based cross-sectional study in a region of Ghana, red cell and platelet counts were signi cantly lower in malaria than non-malaria infected patients (14). Ndamukong-Nyanga et al noted similar ndings in another cross-sectional study in Buea, Cameroon (22). They noted thrombocytopenia and anaemia to be the most signi cant predictors of malaria in their study region and concluded that these parameters could improve malaria diagnosis when utilised in conjunction with other clinical features.…”
Section: Discussionmentioning
confidence: 68%